(untitled) (Journal of Ideas in Health, 2021)
Hemostatic abnormalities had been reported in COVID-19 patients, which may include disseminated intravascular coagulation (DIC), hypercoagulability, and alterations in platelets parameters. Articles that investigate the alterations of hemostatic abnormalities during the COVID-19 disease (2020-2021) and their predictive value of disease outcome have been thoroughly reviewed. Among the reviewed articles, thrombocytopenia is observed in 5.0-41.7% of COVID-19 patients, which is related to disease severity. Moreover, other platelets parameters, including Platelets/lymphocytes ratio (PLR), Mean platelets volume (MPV), and aggregation, may also be affected. On the other hand, findings of coagulation tests such as D dimer; fibrinogen, Antithrombin (AT), and Fibrin degradation products (FDP) are significantly elevated in COVID-19 patients, while in a single study, most of the patients had positive Lupus anticoagulants (LA) and normal protein C (PC). In the same perspective, these alterations showed significant correlations with disease severity. Overall, hemostatic laboratory markers are significant predictors of COVID-19 disease outcome as indicated by the increased risk of venous and arterial thrombotic events, especially in ICU patients.